Real-time PCR assay for the discrimination and quantification of wheat and barley strains of Wheat dwarf virus - Gadiou, S; Ripl, J; Jaňourová, B; Jarošová, J; Kundu, J K (Virus genes, 2012)
A rapid method for detection, discrimination and quantification of wheat and barley strains of wheat dwarf virus (WDV) was successfully developed. The sensitivity of quantification of the wheat and barley strains of WDV ranged from an average of 1.2 × 10(7)-1.2 × 10(2) and from an average of 1.4 × 10(7)-1.4 × 10(4) copies of viral genome, respectively. These standard serial dilutions were applied to plant and vector tissues for virus titer calculations. Both strains of WDV were clearly discriminated by specific probes and melting curve analysis. Both TaqMan(®) and SYBR(®) Green technologies provided accurate and reliable methods for monitoring, detection, discrimination, and quantification of WDV.
Keywords: virová nálož; Plant Diseases; senzitivita a specificita; ječmen (rod); Sensitivity and Specificity; Geminiviridae; Triticum; Real-Time Polymerase Chain Reaction; Viral Load; pšenice; Hordeum; nemoci rostlin; kvantitativní polymerázová řetězová reakce